An update on the genetics of age-related macular degeneration - Scholl, Hendrik P.N. (Molecular Vision, 2007)
Age-related macular degeneration (AMD) is a genetically complex disorder of the photoreceptor-RPE-Bruch's membrane-choriocapillaris complex. Family and twin studies have shown that the susceptibility for this disease is genetically influenced. The heritability has been estimated to be up to 71%. Linkage and association studies have identified several chromosomal regions that are likely to contain susceptibility loci with strongest evidence found on chromosome 1q31 and 10q26. Variants in the complement factor H (CFH) gene have been shown by several independent studies to be associated with an increased risk for AMD in Caucasian populations. These findings imply that the innate immune system may play a significant role in AMD pathogenesis. The LOC387715/HTRA1 locus within 10q26 has been identified as a second major locus contributing to AMD pathogenesis. The two late forms of AMD, choroidal neovascularization and geographic atrophy, have not been found to be different in risk allele distribution. Variants within CFH and LOC387715/HTRA1 may contribute to the increased risk of late AMD largely through their impact on precursors, such as drusen and/or other RPE/Bruch's membrane changes. Considering variants at CFH, LOC387715/HTRA1 and complement component 2-complement factor B (C2-FB), high-risk homozygotes at all three loci may have a 250-fold increased risk compared to baseline. However, the identification of genetic factors has not resulted in therapeutic strategies to modify the disease so far and additional genetic and environmental factors are yet to be discovered in order to influence the onset and the progression of AMD.